As Principais Evidências Acerca dos Conceitos de Logística Urbana: Um Estudo Bibliométrico - Vanessa Teresinha Alves (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2020)
The evolution of cities has changed the transport and cargo distribution systems, causing mobility and logistics problems and requiring the improvement of logistics and transport operations. This article development out a bibliometric study on the main evidence related to the themes of Urban Logistics and Logistics at a global level. The data were collected in the Web of Science database of the Institute for Scientific Information, using as keywords the terms "Logistic" and "Urban Logist" and; delimiting the search from 2008 to 2017. The publications were analyzed for the possibility of being a "Hot Topic", according to the Banks methodology (2006). Most of the publications are in the English language, concentrating on the USA and China, with Brazil being the seventh country with the largest publication. The largest publications were in the areas of Occupational Health, Public Environment and Transport, particularly in the last three years. The theme is recent and incipient in Brazil. Worldwide, it is considered a "Hot Topic" in the following areas: social, economic, environmental, management, international logistics and sustainability, and also, as with the possibility of becoming a "Hot Topic" for others, such as operations and engineering, the latter is an important area for future studies.